Efficacy and safety of the flexible negative-pressure ureteral sheath in retrograde intrarenal surgery: a systematic review and meta-analysis - Wang, Lin; Luo, Zhifang; Huang, Wen; Jia, Qilei (Frontiers in Surgery, 2025)
PurposeTo evaluate the safety and efficacy of the flexible negative-pressure ureteral sheath (FANS) in flexible ureteroscopic lithotripsy (RIRS) for urinary calculi.MethodsComputerized searches were performed in English databases including PubMed, Embase, Web of Science, and the Cochrane Library up to 4 February 2025, to identify clinical studies on the FANS combined with RIRS for urinary calculi. Data analysis and extraction were conducted using Stata 18.0 and Review Manager 5.3 software.ResultsThis meta-analysis of nine studies (1,785 patients) showed that the FANS significantly improved stone-free rates [odds ratio (OR) = 2.58, 95% CI = 2.11–3.15] and reduced intraoperative complications (OR = 0.32, P = 0.02), postoperative complications (OR = 0.37), reoperation (OR = 0.28), and stone basket use (OR = 0.01) when compared with the traditional ureteral access sheath (T-UAS). Subgroup analyses confirmed the superiority of the FANS in removing stones ≤20 mm (OR = 2.10) and >20 mm (OR = 3.03), with shorter operative times for small stones (SMD = −0.31) and Ho:YAG (SMD = −0.63).ConclusionsThe FANS enhances RIRS efficacy and safety by improving stone clearance, reducing complications, and minimizing auxiliary instrument use. While it did not shorten hospitalization or overall operative time, its advantages in removing larger stones and laser compatibility underscore its clinical value. Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier (CRD42024611779).